Digitalization of Activities at Pondok Pesantren Al Ikhlas Lahat Tanjung Sakti through the Application of Information and Communication Technology - Suryati, Suryati; Adisel; Nazarmanto (Al-Ulum, 2025)
This study examines the implementation of information and communication technology (ICT) applications in the management and educational activities of Pondok Pesantren Al Ikhlas Lahat Tanjung Sakti, South Sumatra. The research aims to analyze how digitalization processes support the improvement of administrative effectiveness, learning quality, and institutional management in the context of Islamic boarding schools. Using a descriptive qualitative method, data were collected through observation, interviews, and document analysis. The findings reveal that the application of ICT has transformed various aspects of pesantren management—particularly in communication, documentation, and the delivery of educational materials. However, challenges such as limited digital literacy among teachers and infrastructure constraints remain obstacles to full digital transformation. The study concludes that ICT adoption in pesantren environments can foster transparency, efficiency, and innovation when supported by human resource development and institutional policy alignment.